The prospects and challenges of Kosovo's accession to the EU in light of the EU's policies and priorities - Mexhuani, Burim (Frontiers in Political Science, 2023)
Introduction This paper analyzes the extent to which the EU's involvement in Kosovo's political and economic development has contributed to the country's progress toward democratization and European integration. Methods The study employs a comparative analysis of the EU's engagement with Kosovo versus other Western Balkan countries. It also utilizes a case study approach to identify the unique challenges presented by Kosovo's contested statehood. Data sources include official EU reports, agreements, commentary from experts, and economic indicators. Results The findings show the EU has played a pivotal role in Kosovo through deploying its assistance instruments, facilitating the normalization dialogue with Serbia, and laying out a potential accession path. However, non-recognition by five member states, disputes with Serbia, and struggles meeting EU reform criteria impact Kosovo's integration prospects. Discussion Despite its substantial involvement, the EU faces credibility issues in Kosovo due to ongoing hurdles thwarting Kosovo's advancement toward accession. The EU must increase its leverage over Serbia, incentivize internal reforms, and align member state positions to support Kosovo's European integration. A clearer pathway to membership in Kosovo would reinforce the EU's role in fostering peace, democracy, and prosperity in the Western Balkans.